Strategi Penerapan Reformasi Birokrasi Pada Sekretariat Jenderal Kementerian Koperasi Dan Usaha Kecil Menengah Republik Indonesia - Shefika Candra Kirana; Mawar Mawar (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The implementation of bureaucratic reform at the Secretariat General of the Ministry of Cooperatives and SMEs of the Republic of Indonesia is still seen as an additional task and has not become an integrated part of the strategy to increase efficiency and effectiveness in realizing agency performance, then the organizational and governance restructuring carried out still requires adjustments to tasks and functions in achieving output as expected, then another problem is the still limited professionalism of the apparatus, especially in terms of competence and commitment in implementing bureaucratic reforms. This study aims to identify and analyze the strategy for implementing bureaucratic reform in government institutions, the Office of the Ministry of Cooperatives and SMEs of the Republic of Indonesia, especially the Secretariat General based on Geoff Mulgan's theory, of purpose, environment, direction, action, learning. The method used is descriptive with a qualitative approach. Data collection techniques through interviews, observation, and documentation. The results of the study show that the objective indicators are optimal, namely the leaders of the bureaucratic reform team and employees are trying to increase the value of bureaucratic reform indicators with various activity programs. Environmental indicators are not optimal, due to the lack of human resources in abilities, knowledge, attitudes. The direction indicator is optimal, because employees get guidance and direction from the leader in terms of coordination, communication and motivation. The action indicators have not been optimal, because they are still faced by unresolved obstacles such as the transfer of positions between units and policy changes. In learning indicators that are not optimal, in the performance targets of each individual and organizational performance, the results are still lacking and there are still supervisors who do not reflect the feasibility and appropriateness so that they must be retested in order to realize good practice.